An unfamiliar physeteroid periotic (Cetacea: Odontoceti) from the German middle–late Miocene North Sea basin at Groß Pampau - I. Montañez-Rivera (Fossil Record, 2020)
The Miocene mica clay locality of Groß Pampau, known for numerous and partly spectacular finds of marine mammals is becoming more and more a prominent site that bears the potential to resolve questions regarding taphonomic relationships and to interpret life communities of the ancient North Sea because of its rich faunal assemblage including invertebrates and other remains of various vertebrate organisms. In the present work we describe a right periotic of Physeteroidea with morphological characters so far unknown from other sperm whales. The periotics of the middle Miocene Aulophyseter morricei demonstrate the closest resemblance to the Groß Pampau specimen in their overall appearance and in the general arrangement and proportions of single structures, particularly of the anterior process and pars cochlearis. A great similarity is also documented with periotics of the living sperm whale, Physeter macrocephalus, especially regarding the shape and disposition of the anterior process and the bony element located dorsally to the accessory ossicle. Kogiid periotics differ strongly from that of the Groß Pampau specimen by having an inflated and short anterior process and, typically, three well-defined spines on it. A new taxonomic naming of the Groß Pampau periotic is not appropriate at this stage, although it might demonstrate the existence of a so-far undescribed physeteroid species. Additionally, its systematic position remains yet unclear and it is unknown at this point if it could belong to Hoplocetus ritzi, another physeterid, whose fragments were discovered in the same locality, or to another, already-described taxon, of which the periotic is still unknown.